The synthesis of functionalized bridged polycycles via C–H bond insertion - Shih, Jiun-Le; Chen, Po-An; May, Jeremy A. (Beilstein Journal of Organic Chemistry, 2016)
This review presents examples from the chemical literature of syntheses of bridged-polycyclic products via C–H bond insertion by carbenes and nitrenes. Applications to natural product synthesis, a description of the essential elements in substrate-controlled reactions, and mechanistic details of transformations are presented. Overall, these transformations allow the construction of important ring systems rapidly and efficiently, though additional catalyst development is needed.
Keywords: bridged rings; carbene; cascade reaction; C–H bond insertion; nitrene